IMPLEMENTASI PROGRAM PEMBANGUNAN INFRASTRUKTUR PERDESAAN (PPIP) DI DESA WIRU KECAMATAN BRINGIN KABUPATEN SEMARANG - Fauzyah Rahmah; Ari Subowo (Journal of Public Policy and Management Review, 2017)
The Village Infrastructure Development Program (PPIP) is a basic program of society empowerment, with purpose to increase the society welfare. Wiru Village, Bringin district, Semarang Regency is one of village that’s received the support from PPIP. This research goal is to describe and analyze how the local government of Semarang Regency is implementing The Village Infrastructure Development Program (PPIP) at Wiru Village, by using the qualitative approached with descriptive type. The analysis techniques to acquire data through interview, observation, and support of documents. This research is using the theory by Merilee S. Grindle who said that the driving factors of implementation program consist of three main factors, there are the content of policy and the scope of policy, and the result of implementation can be seen by effects and changes that happened on society. The result has shown that implementation of The Villages Infrastructure Development Program (PPIP) Implementation at Wiru Villages, Bringin District, Semarang Regency received a positive responses from villagers, and a change after access repair of villagers access welfare has simplify and make the mobility of villagers easier. Even thought, the strengthening of villagers institutions that handle the PPIP is still unfulfilled yet because the limit time of program. So of that, the villagers need a soft skills training to make sure that even The Village Infrastructure Development Program (PPIP) has done, the villagers still can utilize that soft skills of PPIP effects.